Design of a small-scale solar Dryer to Improve Natural Drying of Vegetables and Fish - Bukhari, Abdallah A. Alyan1, Mohammed M.; Bukhari, Mohammed M.; Sulieman, Abdel Moneim E. (Gezira Journal of Engineering and Applied Sciences, 2012)
This study aimed at improvement of a solar dryer based on the principle of natural–convection used for drying vegetables and fish. The constructed dryer, comprises of three main models, solar collector (tent of polythene sheet collector), drying chamber and solar chimney. Design has been made to eliminate the problem of quality loss and over drying. Okra, Tomato, onion, fish were subjected to solar drying and open – air drying processes. The chemical, microbiological analyses and sensory evaluation were carried out for the dried products. The results gives indication of improved quality for solar dryer compared to products dried in open – air systems which indicates its efficiency in drying.